Designing 3d metal oxides: selecting optimal density functionals for strongly correlated materials. Issue 23 (20th May 2022) - Østrøm, Ina; Hossain, Md. Anower; Burr, Patrick A.; Hart, Judy N.; Hoex, Bram
Abstract : First-row TMOs have remarkable properties that are appealing in materials design for technological applications. Their electronic structure can be modelled with DFT, but this requires careful considerations due to strong correlation effects of 3d orbitals. Abstract : Transition metal oxides (TMOs) have remarkable physicochemical properties, are non-toxic, and have low cost and high annual production, thus they are commonly studied for various technological applications. Density functional theory (DFT) can help to optimize TMO materials by providing insights into their electronic, optical and thermodynamic properties, and hence into their structure–performance relationships, over a wide range of solid-state structures and compositions. However, this is underpinned by the choice of the exchange–correlation (XC) functional, which is critical to accurately describe the highly localized and correlated 3d-electrons of the transition metals in TMOs. This tutorial review presents a benchmark study of density functionals (DFs), ranging from generalized gradient approximation (GGA) to range-separated hybrids (RSH), with the all-electron def2-TZVP basis set, comparing magneto-electro-optical properties of 3d TMOs against experimental observations. The performance of the DFs is assessed by analyzing the band structure, density of states, magnetic moment, structural static and dynamic parameters, optical properties, spin contamination and computational cost. The results disclose the strengths and weaknesses of the XC functionals, in terms of accuracy, and computational efficiency, suggesting the unprecedented PBE0-1/5 as the best candidate. The findings of this work contribute to necessary developments of XC functionals for periodic systems, and materials science modelling studies, particularly informing how to select the optimal XC functional to obtain the most trustworthy description of the ground-state electron structure of 3d TMOs.